2022
DOI: 10.1242/jcs.259009
|View full text |Cite
|
Sign up to set email alerts
|

Imaging nanoscale nuclear structures with expansion microscopy

Abstract: Commonly applied super-resolution light microscopies have provided insight into subcellular processes at the nanoscale. However, imaging depth, speed, throughput and cost remain significant challenges, reducing the numbers of three-dimensional, nanoscale processes that can be investigated and the number of laboratories able to undertake such analysis. Expansion microscopy solves many of these limitations but its application to imaging nuclear processes has been constrained by concerns of unequal nuclear expans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…2). ChromExM provides markedly higher resolution than previous ExM applications for chromatin imaging (~3 to 15 nm versus ~65 nm) ( 31 ). Other methods to visualize chromatin, such as ChromEMT ( 10 ), lack multimodal labeling, and the resolution of single-molecule localization microscopy is limited by the size of the fluorescent labels (~20 nm for primary and secondary antibody), which becomes negligible in ChromExM given that labels are applied after expansion ( 11 ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…2). ChromExM provides markedly higher resolution than previous ExM applications for chromatin imaging (~3 to 15 nm versus ~65 nm) ( 31 ). Other methods to visualize chromatin, such as ChromEMT ( 10 ), lack multimodal labeling, and the resolution of single-molecule localization microscopy is limited by the size of the fluorescent labels (~20 nm for primary and secondary antibody), which becomes negligible in ChromExM given that labels are applied after expansion ( 11 ).…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have reported conflicting results regarding the isotropy of ~4× to 8× expansion of chromatin ( 31 , 32 ). To address whether chromatin structure is perturbed by physical expansion, we developed an assay in which a pattern of parallel stripes is photocleaved into biotin-labeled DNA before expansion and visualized after expansion (Fig.…”
Section: Chromexm Achieves Single-nucleosome Resolution While Preserv...mentioning
confidence: 97%
“…To date, various strategies has been applied to quantify the distortions of expansion at the macroscopic and nanoscopic levels. Macroscopic expansion is commonly evaluated by comparing the distance variation between two identical sites of the hydrogel pre- and postexpansion. ,,, To assess expansion isotropy at the nanoscale, the most commonly used method is to compare the postexpansion confocal image with the super-resolution image of the same features in unexpanded states (e.g., SIM or d STORM). ,,,, Following a nonrigid registration process between two images, the amount of distortions after expansion can be measured. Expansion distortions can also be evaluated by applying ExM to quantify well-characterized biological targets, e.g., centrioles and nuclear pore complexes, , or well-defined structures, e.g., DNA origami and nanopillars .…”
Section: Expansion Isotropymentioning
confidence: 99%
“…54,58,100,101 To assess expansion isotropy at the nanoscale, the most commonly used method is to compare the postexpansion confocal image with the super-resolution image of the same features in unexpanded states (e.g., SIM or dSTORM). 17,19,54,59,101 Following a nonrigid registration process between two images, the amount of distortions after expansion can be measured. Expansion distortions can also be evaluated by applying ExM to quantify well-characterized biological targets, e.g., centrioles 30 and nuclear pore complexes, 54,100 or well-defined structures, e.g., DNA origami 71 and nanopillars.…”
Section: Expansion Isotropymentioning
confidence: 99%
See 1 more Smart Citation